Bound Morpheme Used In AL JAZEERA News Entitled “SYRIA’S REFUGEE CHILDREN: FUTURES LOST TO THE WAR” by Barbara Bibbo: A Morphology Perspective - Paramita Kusumawardhani (Wanastra: Jurnal Bahasa dan Sastra, 2021)
The purpose of the research is to know about the use of bound morpheme in an article in Al Jazeera News, entitled, “Syria’s Refugee Children: Futures Lost to the War” written by Barbara Bibbo. Bound morpheme is commonly used in some articles because it can change the meaning of the word itself. Bound morpheme is part of derivational morphology. Morphology itself means the study of morphemes which are the smallest significant units of grammar. A morpheme is the smallest unit in English linguistics which form word. There are two kinds of morpheme; they are free morpheme and bound morpheme. Morpheme that can stand on their own are called free, and ones that cannot are bound. A bound morpheme has two types; there are Derivational and inflectional morpheme. The data of the research was taken from an article in Al-Jazeera News. Qualitative descriptive method was used to do the research. The results of the research are there are 49 bound morphemes found in the article. 5 of them are derivational and 44 of them are inflectional.